2000
DOI: 10.4049/jimmunol.165.5.2903
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of Functional 4-1BB (CD137) Ligand on Carcinoma Cells

Abstract: Members of the TNF superfamily, including Fas, Fas ligand, and CD40, have been shown to be expressed on tumor cells. In the studies described in this work, we report that another family member, the ligand for 4-1BB (CD137), is expressed on various human carcinoma cell lines, on cells of solid tumors derived from these cell lines, and cells obtained from human tumors. Expression of 4-1BB ligand (4-1BBL) mRNA was detected by both RT-PCR and Northern blot analysis, and expression of 4-1BBL protein was detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 42 publications
(43 reference statements)
5
94
1
Order By: Relevance
“…Functional expression of 4-1BBL has been described on various healthy cell types including B cells, but also on malignant cells of various origins [16,[20][21][22]. We here analyzed 4-1BBL expression on primary human B-CLL Cells (CD5 1 CD19 1 ) from a total of 56 patients.…”
Section: B-cll Cells Express Functional 4-1bblmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional expression of 4-1BBL has been described on various healthy cell types including B cells, but also on malignant cells of various origins [16,[20][21][22]. We here analyzed 4-1BBL expression on primary human B-CLL Cells (CD5 1 CD19 1 ) from a total of 56 patients.…”
Section: B-cll Cells Express Functional 4-1bblmentioning
confidence: 99%
“…As 4-1BBL signaling can induce release of TNF and IL-8 by malignant cells [16,21] and because the levels of these cytokines correlate with prognosis of CLL patients [23,24] we determined whether the CLL-expressed 4-1BBL was capable to transduce signals resulting in the production of immunomodulatory cytokines. Primary CLL cells of patients were cultured alone or on immobilized 4-1BB-Ig (which enables multimerization of 4-1BBL) with IgG1 serving as the isotype control.…”
Section: B-cll Cells Express Functional 4-1bblmentioning
confidence: 99%
“…13 4-1BBL was also present at high levels in the sera of some patients with hematological diseases 35 as well as on some carcinoma cell lines. 36 The inducible expression pattern of 4-1BBL was similar to that of B7-1 and B7-2 in the CD28:B7 pathway. The costimulatory molecules B7-1 and B7-2 were expressed at very low levels in resting APCs and upregulated upon activation by surface Ig.…”
Section: Expression Of 4-1bb and 4-1bbl In Vivomentioning
confidence: 74%
“…One signal occurs through the TCR:MHC:Ag complex while the other is provided through co-stimulation. T cell will be anergic in response to one signal alone if co-stimulation is absent (2,3,5). A number of studies have demonstrated effective anti-tumor targeting in clinical trials using the co-stimulatory molecules but to date these have almost utilized the B7:CD28 pathway (17).…”
Section: Discussionmentioning
confidence: 99%
“…These T cells then receive a second set of signals on binding of their co-stimulatory molecules to the corresponding molecular pairs on the APCs, and the T cells become activated. Without co-stimulation, T cells will undergo apoptosis or become anergic (2)(3)(4)(5)(6). The fact that tumor cells are found to have low co-stimulatory molecule expression may explain how tumor cells evade the immune system.…”
Section: Introductionmentioning
confidence: 99%